PENGARUH KONSENTRASI HORMON Indole Butyric Acid (IBA) DAN LAMA PERENDAMAN TERHADAP KECEPATAN PERTUMBUHAN TUNAS STEK AKAR CENDANA (Santalum album Linn.) PADA MEDIA PASIR - , FITRIANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Population of sandalwood trees in the moment was more less and even almost rare. Need to rehabilitation with planting sandalwood trees. Supplying quality seedling with vegetative propagation of sandalwood root cutting as alternative vegetative propagation to anticipated gain dificulty of seed and undifinited fruit monsoon and blomming monsoon sandalwood trees in every place. Purpose of this study is to know the correction of plant regulator hormone concentration so that sandalwood root cutting shooting quickly and to know optimum soaking time. Study was conducted in Silviculture Intensive Nursery Faculty of Forestry Gadjah Mada University in Klebengan. The design of the experiment was Customized Random Design which repeated twelve time using factorial treatment with two factor that is IBA hormone concentration ( 0 ppm, 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, 1000 ppm) and soaking time (30 minute, 40 minute, 50 minute). Parameter is monitoring are speed of shoot growth, shoot number, shoot high, and percentage of root cutting shooting. Data analysis was conducted by Diskriptip Kuantitatif and then presented in table and chart. Result of this study showed that soaking time 30 minute give the best effect for shoot growth speeding, shoot number, shoot high and percentage of shooting root cutting while IBA hormone concentration have positive effect for shooting growth is hormone concentration 200 ppm. Shoot was growth in date of 28 after planting in rooting medium and resulting shoot high in last monitoring 9, 22 cm, in concentration 100 ppm resulting shoot number 21 shoots and in concentration 300 ppm resulting percentage of root cutting shooting 75%.